A CRISPR/Cas12a-assisted rapid detection platform by biosensing the apxIVA of Actinobacillus pleuropneumoniae - Luan, Tian; Wang, Lu; Zhao, Jiyu; Luan, Hui; Zhang, Yueling; Wang, Chunlai; Langford, Paul R.; Liu, Siguo; Zhang, Wanjiang; Li, Gang (Frontiers in Microbiology, 2022)
Actinobacillus pleuropneumoniae is an important respiratory pig pathogen that causes substantial losses in the worldwide swine industry. Chronic or subclinical infection with no apparent clinical symptoms, poses a challenge for preventing transmission between herds, and acute death often occurs. Rapid diagnostics is important for the control of epidemic disease. In this study, we have formulated an A. pleuropneumoniae species-specific apxIVA-based CRISPR/Cas12a-assisted rapid detection platform (Card) which combines recombinase polymerase amplification (RPA) of target DNA and subsequent Cas12a ssDNase activation. Card has a detection limit of 10 CFUs of A. pleuropneumoniae, and there is no cross-reactivity with other common swine pathogens. The detection process can be completed in 1 hour, and there was 100% agreement between conventional apxIVA-based PCR and Card in detecting A. pleuropneumoniae in lung samples. Microplate fluorescence readout enables high-throughput use in diagnostic laboratories, and naked eye and lateral flow test readouts enable use at the point-of-care. We conclude that Card is a versatile, rapid, accurate molecular diagnostic platform suitable for use in both laboratory and low-resource settings.